EMOTIONAL INTELLIGENCE IN ANCIENT SCIENCE WITH SPECIAL REFERENCE TO CHARAK SAMHITA AND SHRIMAD BHAGWAD GITA - Arora, Nishi; Kumar, Praveen (International Journal of Research -GRANTHAALAYAH, 2018)
The author first introduces emotion, later adding that the essence of the Ancient psychology and psychology of contemporary times are practically similar to a fault disregarding the discrepancies in languages and terms. The paper is condensed to the pathology behind emotional disruptions, the general principal of combating the same and prevention of emotional imbalance (deviation of emotional intelligence). EQ is said to be objectively more important than IQ in many ways according to the reasoning that emotional intelligence is tied to cognition and emotional imbalance can create difficulties in the social and individual lives of people, causing reduction in productivity. The root causes of emotional imbalances are the imbalance of the three elements of mind: Sattva (similar to Super ego), Rajas (similar to Ego) and Tamas (similar to Id). Charak Samhita has explained the origin of Emotional turmoil, and various techniques to prevent and treat them. Shrimad Bhagwad Gita is a universal philosophy that has touched almost every aspect of human psychology, especially emotions.